The CpxAR Two-Component System Contributes to Growth, Stress Resistance, and Virulence of Actinobacillus pleuropneumoniae by Upregulating wecA Transcription - Yan, Kang; Liu, Ting; Duan, Benzhen; Liu, Feng; Cao, Manman; Peng, Wei; Dai, Qi; Chen, Huanchun; Yuan, Fangyan; Bei, Weicheng (Frontiers in Microbiology, 2020)
Actinobacillus pleuropneumoniae is the pathogen of porcine contagious pleuropneumonia. In A. pleuropneumoniae, the CpxAR two-component system is essential for fitness and growth. The O-antigen protrudes from the outer membrane to the exterior of the cell, and the outer membrane serves as a barrier that helps the bacteria to survive in harsh environments. WecA, a undecaprenyl phosphate GlcNAc-1-phosphate transferase, is involved in O-antigen repeating unit biosynthesis. In this study, we investigated the role of CpxAR in the expression of wecA in A. pleuropneumoniae. Our results revealed that CpxR positively regulates wecA expression by directly binding to the putative promoter region of wecA. Wild-type, ΔcpxAR, ΔwecA, and complemented strains were investigated under serum, oxidative, and osmotic stresses. The ΔcpxAR and ΔwecA strains were more susceptible to these stresses than the wild-type, but the complemented strains showed phenotypes similar to those of the wild-type. Mice infected with the ΔcpxAR and ΔwecA strains exhibited lower mortality and bacterial loads in the lung than those infected with the wild-type or complemented strains. This study reveals that the CpxAR two-component system contributes to A. pleuropneumoniae growth, stress resistance, and virulence, by upregulating expression of wecA. Our findings provide new insight into the pathogenesis of A. pleuropneumoniae.